Production Optimization of Palm Using Simplex Method - Rizal, Rizal; Wahyudien, Mohammad Arief Nur; Ahistasari, Asih; Tajuddin, Tamrin; Maulana, Mirga Maulana (Industrial Engineering Journal – System, 2023)
The PWJ Brown Sugar Factory is one of the MSME industries which operates in the F&B production sector, mainly brown sugar production. Sales at this factory often change every month. Therefore, it is necessary to plan production quantities so there are no excesses or shortages when producing brown sugar. According to available resources, this research aims to optimize production and profits in making brown sugar at the PWJ Brown Sugar Factory. To maximize profits, the simplex linear programming method will be used. The linear programming method helps companies by combining product variations based on the company's limited resources. In this research, the data calculation process to maximize profits was carried out using the Microsoft Excel application. Data collection carried out in this research was through direct interviews with brown sugar factory owners in the Sorong Regency area. Next, the data is processed using a linear program, especially the simplex method. This research discusses two types of brown sugar: type A and type B. The price of brown sugar in this factory is 18,000-22,000/kg. The maximum profit at the PWJ Brown Sugar Factory will be obtained when producing 15 kilograms of type A brown sugar and 12kg of type B with a total income of Rp. 546,000-. This research can still be developed, so it is recommended for future researchers to use other applications as comparison material.